Detection and Severity Assessment of Temporomandibular Joint Osteoarthritic Changes in Patients with Temporomandibular Disorders Using CBCT - Kharman Khidhr Rahman; Shahen Ali Ahmed; Sarkawt Hamad Ali; Khoshee Salh Hamed (Erbil Dental Journal, 2024)
Background and objectives: Osteoarthritis refers to a non-inflammatory condition often linked to aging. It involves the gradual breakdown of bone, cartilage, and surrounding soft tissues around the joints. The aim of this study is to detect osteoarthritic change in patients with temporomandibular disorder, to determine the severity of osteoarthritic changes, and to assess the relation of gender and age with the severity prevalence of temporomandibular joint osteoarthritis.